Random access networks with separable schemes. Issue 4 (1st July 2019) - Ganesan, Ghurumuruhan
Abstract : Consider a time slotted multiuser random access network where M users have access to a single channel and each user attempts to send packets in a particular time slot with a certain probability, according to a predetermined access scheme. This forms an interacting system of queues and in this study, the authors consider generic access schemes that satisfy a separability condition and obtain bounds for the stability region, directly using a Lyapunov‐type analysis. They apply their results to the case of random access networks with partial conflicts where any particular user has collision conflicts with only a subset of the other users. Using conflict graphs to quantify the degree of such conflicts, they obtain bounds for the stability region for both deterministic and random conflict graphs that model, respectively, static and mobile networks.